Phytochemical variations antioxidant, and antibacterial activities among zebaria sumac (Rhus coriaria var. zebaria) populations in Iraq - Saba Shahrivari; Saeed Mizgeen Saeed Zeebaree; Saeideh Alizadeh-Salteh; Hadar S. Feizy; Mohammad Reza Morshedloo (Scientific Reports, 2024)
Abstract Sumac (Rhus coriaria L.) is one of the medicinal plants of Anacardiaceae family and widely used as a spice in Iran and Arab countries. Rhus coriaria var. zebaria is a small tree or large shrub, wildly growing in Iraq and described as a new variety with special characteristics. These increase the importance of studying sumac in these areas. Here, the phytochemical variations and the antibacterial activity of 50 accessions of this variety from five different climatic conditions was evaluated in order to identify the best accession to use and the best area for its cultivation. This is the most comprehensive study on this plant. Essential oil compounds were identified using GC–MS method and according to the results, Z, E-2,13-octadecadien, caryophyllene oxide, 2,4-decadienal, E-caryophyllene and nonanoic acid were among the main compounds. Also, the variety is a rich source of minerals including K, Ca, Mg, Na, P, and N. Sumac fruit extract from Akre Xerds had the highest anthocyanin and the lowest amount was from Kavilca region. The radical scavenging effect of extract from Dostic area in the concentration of 400 µg/mL is closer to the effect of ascorbic acid. The largest inhibition was found in the sumac extracted oil of Xasto Zhere area against S. aureus in compared with penicillin and amoxicillin and enrofloxacin antibiotics.